Physicochemical characterization and cosmetic applications of Passiflora nitida Kunth leaf extract (Brazilian Journal of Pharmaceutical Sciences, 2022)
Passiflora nitida Kunth, an Amazonian Passiflora species, is little studied, although the specie’s high biological potential. Herein the plant’s pharmacognostic characterization, extract production, antioxidant potential evaluation, and application of this extract in cosmetic products is reported. The physical chemical parameters analyzed were particle size by sieve analysis, loss through drying, extractive yield, total ash content, laser granulometry, specific surface area and pore diameter (SBET), differential scanning calorimetry, thermogravimetry (TG), and wave dispersive X-Ray fluorescence (WDXRF). Total phenol/flavonoid content, LC-MS/MS analysis, DPPH and ABTS antioxidant radical assays, cytotoxicity, melanin, and tyrosinase inhibition in melanocytes test provided evidence to determine the content of the major constituent. P. nitida dry extract provided a fine powder with mesopores determined by SBET, with the TG curve showing five stages of mass loss. The antioxidant potential ranged between 23.5-31.5 mg∙mL-1 and tyrosinase inhibition between 400-654 μg∙mL-1. The species presented an antimelanogenic effect and an inhibitory activity of cellular tyrosinase (26.6%) at 25 µg/mL. The LC-MS/MS analysis of the spray-dried extract displayed the main and minor phenolic compounds constituting this sample. The results indicate that P. nitida extract has promising features for the development of cosmetic formulations.